Type material of Cicadellinae (Hemiptera: Cicadellidae) of the Museum für Naturkunde, Humboldt-Universität zu Berlin, Germany - Lozada, Pedro W. (2016)
In this paper, 65 type species of Cicadellinae (Hemiptera: Cicadellidae) are reported from the collections of the Museum für Naturkunde, Universität Humboldt, Berlin, Germany, described by Signoret, Breddin, Schmidt, Jacobi, Schröder, Burmeister and Emmrich. The species of Melichar have not been included because Wilson & Takiya (2007) reported them as present in the Hungarian Natural History Museum.